2018
DOI: 10.1002/cbic.201700642
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Light‐Controlled Gene Expression and Protein Targeting in Neurons and Non‐neuronal Cells

Abstract: Near-infrared (NIR) light-inducible binding of bacterial phytochrome BphP1 to its engineered partner, QPAS1, is used for optical protein regulation in mammalian cells. However, there are no data on the application of the BphP1-QPAS1 pair in cells derived from various mammalian tissues. Here, we tested the functionality of two BphP1-QPAS1-based optogenetic tools-an NIR- and blue-light-sensing system for control of protein localization (iRIS) and an NIR light-sensing system for transcription activation (TA)-in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…It has been shown that a two-component FR–NIR optogenetic system based on the heterodimerization of a RpBphP1 bacterial phytochrome with its binding partner RpPpsR2 is spectrally compatible with LOV-based optogenetic tools, enabling simultaneous regulation of several processes in a cell 30,31 . Our current results indicate that the FR–NIR light sensitivity of the DrBphP-based opto-kinases also allows their crosstalk-free combination with the visible-light optogenetic tools and fluorescent proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a two-component FR–NIR optogenetic system based on the heterodimerization of a RpBphP1 bacterial phytochrome with its binding partner RpPpsR2 is spectrally compatible with LOV-based optogenetic tools, enabling simultaneous regulation of several processes in a cell 30,31 . Our current results indicate that the FR–NIR light sensitivity of the DrBphP-based opto-kinases also allows their crosstalk-free combination with the visible-light optogenetic tools and fluorescent proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Combining optogenetic tools controlled by light of different wavelengths enabled tridirectional protein targeting 27 , which may be used to control multifunctional proteins or to increase dynamic range of bidirectional localizers, as discussed 31 . A NIR-blue-light inducible shuttle (iRIS) construct was shown to be effective for dualwavelength-controlled exogenous protein relocalization 16,19 . In this system, the QPAS1 protein is fused to a blue-light-sensing AsLOV2-based nuclear localization controller.…”
Section: Resultsmentioning
confidence: 99%
“…Blue-light-mediated genome editing was reported recently 17 . The non-opsin optogenetic tools are used in cultured cells of various origin 18 , in primary cell cultures 19 and in vivo 20 . Although the optogenetic systems to regulate protein-protein interactions demonstrated high spatiotemporal precision and large dynamic range of responces 21,22 , they usually control functions of the overexpressed exogenous proteins.…”
mentioning
confidence: 99%
“…Upon illumination, activated BphP1 binds to PpsR2 and releases the promoter under its repression. UV light is harmful to cells while near-infrared signals can penetrate tissues (Chen et al, 2018 ), which enables applications of the BphP1/PpsR2 system in mammalian cells (Kaberniuk et al, 2016 ; Redchuk et al, 2017 , 2018b ).…”
Section: Light Sensors In Bacteriamentioning
confidence: 99%